Chin Contour Changes After Transoral Endoscopic Thyroidectomy: Aesthetic Outcomes, Risk Factors, and Patient Satisfaction - Zedan, Mohamed Hamdallah; Hossam, Eslam; Kandil, Emad; Mohsen, Amr; Wahab Amin, Ayman Abdel (Journal of Neonatal Surgery, 2025)
Background: Transoral Endoscopic Thyroidectomy via the Vestibular Approach (TOETVA) provides a scarless alternative to conventional thyroid surgery. However, the potential for postoperative alterations in lower facial contour, particularly chin asymmetry, remains underexplored. Objective: This study aimed to examine the incidence, severity, and resolution of postoperative chin asymmetry following TOETVA and to evaluate its effect on patient satisfaction. Methods: A prospective observational study was conducted at the National Cancer Institute, Cairo University, from 2023 to 2025. Thirty-one patients undergoing TOETVA for benign or indeterminate thyroid nodules (≤4 cm) were included. Postoperative chin asymmetry was clinically assessed at 1 and 3 months by two independent surgeons. Patient satisfaction with cosmetic outcomes was measured using a 10-point Likert scale. Comparative analyses were performed to explore associations between asymmetry and demographic or operative variables. Results: Chin asymmetry was observed in 16.1% (5/31) of patients at one month, all cases being mild and resolving spontaneously by three months. Loss of chin dimple occurred in two patients (6.4%). No mental nerve injuries or sensory deficits were reported. Patients with asymmetry exhibited trends toward lower body mass index (BMI), longer operative times, and larger nodules, though these associations were not statistically significant. The mean satisfaction score was high (8.7 ± 1.1), with 90% of patients rating their chin appearance ≥8/10, including those with transient asymmetry. Conclusions: Mild, transient chin asymmetry is a relatively frequent but self-limiting occurrence after TOETVA and does not significantly diminish patient satisfaction. Preoperative counseling should address potential alterations in chin contour, especially in patients with preexisting dimples.